The engineering of knowledge-based systems : theory and practice - Gonzalez, Avelino J.; Dankel, Douglas D. (Englewood Cliffs, N.J. : Prentice Hall, 1993)
This volume provides the most comprehensive single-volume coverage of both the theory and the practical applications of knowledge-based systems. Authors Avelino J. Gonzalez and Douglas D. Dankel cover the theoretical foundations of knowledge-based systems as a branch of artificial intelligence, and then concentrate on practical aspects of a knowledge-based system development and implementation. Emphasizing a hands-on approach,'The Engineering of Knowledge-Based Systems, Theory and Practice: a) Bases the discussion of knowledge-based systems development on the software engineering life-cycle approach; b) Features a highly accessible presentation throughout, even when describing complex issues such as uncertainty management; and c) Provides easy-to-use, real-world tools.
Introduction to Knowledge-based Systems -- Knowledge-based Systems Structure -- Logic and Automated Reasoning -- Introduction to Rule-based Reasoning-- Details of Rule-based Reasoning -- Associative Networks, Frames, and Objects -- Blackboard Architectures -- Uncertainty Management -- Advanced Reasoning Techniques -- The Knowledge-based System Lifecycle -- Feasibility Analysis -- Requirements Specification and Design -- Knowledge Acquisition and System Implementation -- Practical Considerations in Knowledge Acquisition -- Alternative Knowledge Acquisition Means -- Verification and Validation -- Legal Issues in Knowledge-based Systems --- Appendix A. The CLIPS System --- Appendix B. The Personal Consultant Plus Shell System.
'An Alan R. Apt book.'
System requirements for computer disks: IBM PC, XT, AT or compatible; PC/MS-DOS 3.3.
Computer disk contains the CLIPS program and a demonstration version of Personal Consultant Plus.
This book not included by cd.
Includes bibliographical references (p. 501-514) and index.
Keywords: Expert systems (Computer science).; Expert systems